Diagnostic and Management of Idiophatic Panhypopituitarism A Case Report - Komang Agus Wira Nugraha; Ida Bagus Aditya Nugraha; Anak Agung Gede Budhiarta; Ketut Suastika; Wira Gotera; Made Ratna Saraswati; I Made Pande Dwipayana; I Made Siswadi Semadi (PP PERKENI, 2024)
Hypopituitarism is marked by decreased secretion of one, several, or all anterior or posterior pituitary hormones. A rare disorder, panhypopituitarism indicates the loss of all the pituitary hormones but often is used in clinical practice to describe a patient's deficiency in growth hormone, gonadotropins, corticotropin, and thyrotropin in whom the posterior pituitary function remains intact. Hypopituitarism may occur because of diverse etiologies and lead to substantial morbidity and mortality. Despite advances in the diagnosis and management of pituitary disorders, hypopituitarism is still associated with increased long-term cardiovascular mortality. We report a rare case of a 22-year-old boy with idiopathic panhypopituitarism. The patient has deficiency of growth hormone, gonadotropin, corticotropin, and thyrotropin, yet the underlying etiology remains unknown in this patient because of lack of imaging data. This is very challenging to do prompt diagnosis and management of panhypopituitarism. The management is needing multiple hormonereplacement therapy, based on the result of pituitary hormone laboratory examination. Prompt treatment is needed to prevent further morbidity and mortality in this patient. hypothyroidism, growth hormon